Overborrowing, underborrowing, and macroprudential policy - Fernando Arce; Julien Bengui; Javier Bianchi (Federal Reserve Bank of Chicago, 2023)
In this paper, we revisit the scope for macroprudential policy in production economies with pecuniary externalities and collateral constraints. We study competitive equilibria and constrained-efficient equilibria and examine the extent to which the gap between the two depends on the production structure and the policy instruments available to the planner. We argue that macroprudential policy is desirable regardless of whether the competitive equilibrium features more or less borrowing than the constrained-efficient equilibrium. In our quantitative analysis, macroprudential taxes on borrowing turn out to be larger when the government has access to ex-post stabilization policies.
Keywords: E58; F31; F32; F34; 330; Macroprudential policy; over-borrowing; under-borrowing